Mechanism of antimicrobial resistance in Shigella isolates - Mehata, S; Duan, GC; Zhang, WD (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Shigellosis still remains a public health problem in developing countries because of poverty, poor sanitation, personal hygiene and poor water supply. Antimicrobial therapy for shigellosis reduces the duration and severity of the disease and can also prevent potentially lethal complications. However, over the past few decades Shigella spp. has become resistant to most of the widely used antimicrobials. This study assessed the patterns of antimicrobial susceptibility and mutations in marA and marR genes of Shigella isolates and its association. MATERIALS AND METHODS: Fifty three isolates of Shigella spp. were tested to evaluate the antimicrobial susceptibility by disc diffusion method (Kirby-Bauer) according to the Clinical Laboratory Standard Institute (CLSI) for the following antimicrobials: ciprofloxacin, norfloxacin, ampicillin, tetracycline, chloramphenicol, trimethoprim, gentamicin and streptomycin and mutation on marAR genes by using polymerase chain reaction–Single strand conformation polymorphism analysis. RESULTS: Study revealed that there was significant association in between resistant to ciprofloxacin, norfloxacin and gentamicin with mutation in marA gene (87.5% vs 51.1%, P<0.05; 87.5%Vs 51.1%, P<0.05 and 90% vs 48.8%, P<0.05, respectively). However, there was no significant association in between resistant to tetracycline, streptocycin and ampicillin. Similarly, it was noted that the association in between antimicrobial resistance with mutation in marR like ciprofloxacin (O% vs 57.8%, P<0.05); norfloxacin (O% vs 57.8%, P<0.05), chloramphenicol (O% vs 70.3%, P<0.05); gentamicin (O% vs 60.5%, P<0.05) and trimethoprim (42.6% vs 100%, P<0.05), suggest that mutation in marR is protective factor for antimicrobial resistance. CONCLUSIONS: The study revealed that mutation in marR is preventive factors for antimicrobial resistance like ciprofloxacin, norfloxacin, chloramphenicol, gentamicin and trimethoprim. DOI: http://dx.doi.org/10.3126/ijim.v1i2.7406 Int J Infect Microbiol 2012;1(1):43-48